Modulation of a coordination structure in a europium(iii)-based metallo-supramolecular polymer for high proton conduction. Issue 65 (5th November 2018) - Narayana, Yemineni S. L. V.; Chakraborty, Chanchal; Rana, Utpal; Ninomiya, Yoshikazu; Yoshida, Takefumi; Higuchi, Masayoshi
Abstract : Developing high proton conducting solid materials is significant in the field of fuel cells. We firstly synthesized europium(iii )-based metallo-supramolecular polymer with uncoordinated carboxylic acids (PolyEu-H ), for high proton conduction. Abstract : Developing high proton conducting solid materials is significant in the field of fuel cells. A europium(iii )-based metallo-supramolecular polymer with uncoordinated carboxylic acids (PolyEu-H ) was successfully synthesized by modifying the synthesis conditions. The proton conductivity was enhanced with increasing the relative humidity (RH) from 30 to 95% RH.PolyEu-H showed about 10 4 times higher proton conductivity than the polymer with coordinated carboxylic acids (PolyEu ) and about 400 times higher than the polymer without carboxylic acids (PolyEu-2 ). The proton conductivity ofPolyEu-H reached 4.45 × 10 −2 S cm −1 at 95% RH and 25 °C and 5.6 × 10 −2 S cm −1 at 75 °C. The activation energy, E a was ultralow (0.04 eV), which indicates proton conduction based on the Grotthuss mechanism. The results indicate that efficient proton conduction occurs through proton channels formed by moisture inPolyEu-H .